Strategi Media Sosial untuk Personal Branding Tokoh Politik pada Pemilu 2024 - Harun, Harun (Jurnal Dinamika Ilmu Komunikasi, 2025)
This study analyzes the influence of social media use by legislative candidates in Bogor Regency, focusing on the personal branding strategies of Hasan Haikal Thalib and Santi Yuliawati Sandali in the 2024 Election. Despite their efforts, both candidates from PPP and PKB have not significantly improved their popularity or electability, remaining behind fellow party candidates Ramli (PPP) and Fuad Al Anshori (PKB). The research aims to examine how these candidates utilize Facebook, Instagram, TikTok, and WhatsApp to construct their personal branding in political campaigns. Adopting a qualitative paradigm with a constructivist perspective and case study approach, the study applies three stages of data analysis: data reduction, data presentation, and conclusion drawing. The findings reveal that both candidates employ social media strategies centered on presenting themselves as community-oriented leaders. Their branding highlights concern for MSMEs, gender equality, religious values, and strong engagement with diverse social groups, including religious figures, mass organizations, and local communities. Through visual content such as videos and photos, they seek to create memorable campaign moments that reinforce their identity. Overall, the study underscores how personal branding through social media serves as a key yet insufficient factor in shaping political competitiveness in local elections.